MEMBANGUN KOMUNIKASI INTIM PASANGAN MUSLIM NIKAH MUDA DALAM PENDEKATAN PSIKOLOGI PERKEMBANGAN DAN AGAMA - Yunita Sari (Psympathic : Jurnal Ilmiah Psikologi, 2008)
Marriage in young people becomes popular among moslem in Indonesian. Unfortunately, the statistic of divorce is also increases every year. Divorce much happen among couples at the first five years of marriage. Communication is the major cause of the divorce. Developmental Psychology approach assumes that couple can built healthy communication with full of affection through confirmation, self disclosure and sexual communication. Furthermore, Islam suggests the moslem  to take Rasulullah (prophet Muhammad Saw.) as their model in the ways of his communication among his family members. The two perspectives can be developed as intervention technique to reduce the statistic of divorce in Indonesia.